Euphemisms in President Joko Widodo’s Speech on the New Normal. - Yuliyanto, Andik; Abrian, Rizky (Jurnal Pena Indonesia, 2023)
The Covid-19 pandemic has transformed the lives of people worldwide. All human activities have since changed in order to protect themselves from the outbreak. Human social activities have been restricted, and individual habits have also changed. These new aspects of life have given rise to the term "new normal." The term "new normal" has been affirmed by the Indonesian government through President Joko Widodo’s speech, which explained Indonesia’s preparation for embracing the new normal. This research aims to analyze the forms of euphemisms found in President Joko Widodo’s speech on the new normal and identify the functions of these euphemisms. The study adopts a qualitative descriptive approach using the method of equivalence and referential equivalence technique. Based on the research findings, there are five forms of euphemisms: (1) circumlocution, (2) borrowing words, (3) using foreign terms, (4) using abbreviations, and (5) one-for-one substitution. The functions of using euphemisms in the speech are as social functions of language and as crisis communication strategies.